2017
DOI: 10.5747/ca.2017.v13.n3.a174
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades Físicas De Um Argissolo Após Fertirrigação Com Vinhaça E Sistemas De Colheita Da Cana De Açucar

Abstract: RESUMOO objetivo deste trabalho foi monitorar alterações no teor de matéria orgânica e nas propriedades físicas de um Argissolo após a fertirrigação com vinhaça e diferentes sistemas de colheita da cana de açúcar, no oeste paulista. A coleta de dados ocorreu em uma empresa de bioenergia de Presidente Prudente, SP, seguindo o delineamento inteiramente casualizado, em esquema fatorial 5x5, caracterizado pelos manejos sem aplicação de vinhaça e colheita de cana sem queima; com aplicação de vinhaça e colheita de c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Considering that biocarbon constitutes a hotspot and presents high Ca, Mg, and Zn amounts, pH values that reach 10.0, microaerophilic conditions and higher temperatures than the adjacent soil, the increased abundance of this subgroup in the vinasse treatment suggests that soil microhabitats in fields treated with this residue provide adequate physical and chemical conditions for the development of these bacteria (Kuzyakov and Blagodatskaya, 2015). Studies have indicated that the application of vinasse for a short period of time in the soil can reduce the water infiltration rate and total porosity due to the cementing effect of OM (Dalri et al, 2010; dos Santos et al, 2017), suggesting that the addition of vinasse may alter the soil aggregate structure. Chloracidobacterium thermophilum , a representative of subgroup Gp4 isolated from hot springs, is microaerophilic and presents optimal growth at a temperature of 5°C and pH ranging from 5.0 to 7.0 (Tank and Bryant, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that biocarbon constitutes a hotspot and presents high Ca, Mg, and Zn amounts, pH values that reach 10.0, microaerophilic conditions and higher temperatures than the adjacent soil, the increased abundance of this subgroup in the vinasse treatment suggests that soil microhabitats in fields treated with this residue provide adequate physical and chemical conditions for the development of these bacteria (Kuzyakov and Blagodatskaya, 2015). Studies have indicated that the application of vinasse for a short period of time in the soil can reduce the water infiltration rate and total porosity due to the cementing effect of OM (Dalri et al, 2010; dos Santos et al, 2017), suggesting that the addition of vinasse may alter the soil aggregate structure. Chloracidobacterium thermophilum , a representative of subgroup Gp4 isolated from hot springs, is microaerophilic and presents optimal growth at a temperature of 5°C and pH ranging from 5.0 to 7.0 (Tank and Bryant, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although the soil subjected to vinasse application in this study had chemical characteristics very similar to that of pasture soils (Naether et al, 2012; Navarrete et al, 2015b), subgroup Gp18 was the least abundant in the NV treatment. Physical factors that can be altered in the presence of vinasse and in the pasture, such as soil moisture and aeration (Dedecek et al, 2000; Silva Filho et al, 2010; dos Santos et al, 2017), may have influenced the occurrence of the Gp18 subgroup. In the conversion of forest to pasture, Gp13 decreases significantly (Navarrete et al, 2015b), suggesting that the ecological role of these microorganisms in natural environments is important.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that biocarbon constitutes a hotspot and presents high Ca, Mg and Zn amounts, pH values that reach 10.0, microaerophilic conditions and higher temperatures than the adjacent soil, the increased abundance of this subgroup in the vinasse treatment suggests that soil microhabitats in fields treated with this residue provide adequate physical and chemical conditions for the development of these bacteria (Kuzyakov and Blagodatskaya, 2015). Studies have indicated that the application of vinasse for a short period in the soil can reduce the water infiltration rate and total porosity due to the cementing effect of OM (Dalri et al, 2010;dos Santos et al, 2017),…”
Section: Discussionmentioning
confidence: 99%
“…Although the soil subjected to vinasse application in this study had chemical characteristics very similar to that of pasture soils (Navarrete et al, 2015b;Naether et al, 2012), subgroup Gp18 was the least abundant in the NV treatment. Physical factors that can be altered in the presence of vinasse and the pasture, such as soil moisture and aeration (dos Santos et al, 2017;Silva Filho et al, 2010;Dedecek et al, 2000), may have influenced the occurrence of the Gp18 subgroup. In the conversion of forest to pasture, Gp13 decreases significantly (Navarrete et al, 2015b), suggesting that the ecological role of these microorganisms in natural environments is important.…”
Section: Discussionmentioning
confidence: 99%